2014
DOI: 10.1038/pcan.2014.36
|View full text |Cite
|
Sign up to set email alerts
|

Association of variants in genes related to the immune response and obesity with BPH in CLUE II

Abstract: BACKGROUNDChronic inflammation and obesity may contribute to the genesis or progression of benign prostatic hyperplasia (BPH) and BPH-associated lower urinary tract symptoms (LUTS). The influence of variants in genes related to these states on BPH has not been studied extensively. Thus, we evaluated the association of 17 single nucleotide polymorphisms (SNPs) in immune response genes (IL1B, IL6, IL8, IL10, TNF, CRP, TLR4, RNASEL) and genes involved in obesity, including insulin regulation (LEP, ADIPOQ, PPARG, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The demographic information of the study populations is shown in Table . The detailed characteristics of the CLUE II study population and Finnish population have been described in previous studies …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The demographic information of the study populations is shown in Table . The detailed characteristics of the CLUE II study population and Finnish population have been described in previous studies …”
Section: Resultsmentioning
confidence: 99%
“…The detailed characteristics of the CLUE II study population and Finnish population have been described in previous studies. 17,19,20 To initially identify candidate genetic variants in the form of SNPs that may be associated with BPH/LUTS, we performed GWAS Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…41 Although some individuals of NA/AN descent were included, they ultimately comprised 1.3% of the non-African American cohort, or 300 individuals. The inclusion of even fewer NA/ANs is seen in other large historical cohort studies, such as the CLUE II cohort, which was 98.8% White, 42 or the National Institutes of Health-American Association of Retired Persons Diet and Health Study, which was 99% White, Hispanic, and African American, with the remaining 1% labeled as Asian/other. 43 A full list of population-level studies in the United States that have not included NA/AN populations is outside the scope of this article.…”
Section: The State Of Population-level Research In Na/an Patients Wit...mentioning
confidence: 99%